PERKEMBANGAN TEORI MANAJEMEN DARI PEMIKIRAN SCIENTIFIC MANAGEMENT HINGGA ERA MODERN SUATU TINJAUAN PUSTAKA - Isnaeni Rokhayati (Fakultas Ekonomi Universitas Pekalongan, 2015)
This paper is a review of the literature or a summary of a variety of management science movement of thought that emerged from the era of the industrial revolution, namely scientific management to today's modern era. The method used in this paper is a review of the literature or literature review with management science thinking. In this study the movement of thought in management science can be grouped into five areas of thought or theory. This is the fifth thought Scientific Management Theory, Administrative Management Theory, Behavioral Management Theory, Quantitative Management Theory, and Modern Management Theory. Of its development in the modern era in the management science can also be divided into three approaches, namely Contingency approuch (situation approach), System approuch, and Dynamic Engagement approuch. The movement of thought presented by the emergence of the idea that first appeared and followed another movement, although in the era of an emerging movement of thought could have another thought. The results of the study and review of the literature review of the literature shows that the development of management thinking starts from the idea of the technical and productivity in manufacturing and developing the ideas associated with nature and human behavior and the relationship between man and sisitem organization. In this paper the study also found an underdeveloped thoughts on the development of business management issues, the management of marketing, financial management, and strategic management. Keywords : development, Scientific management , modern management, contingency approach, system approach, dynamic approach to engagement.